Design and Synthesis of Organic Functional Materials for Energy Conversion and Storage Applications - Lin, Francis (My University, 2020)
Carbon emission from consumption of fossil fuels has led to global warming accompanying with a large number of environmental issues. In order to lessen the strong dependence on fossil fuels in modern society, it is crucial to develop new energy sources which are clean, renewable and environmentally friendly. Solar energy is one of the leading candidates to fulfill the foreseeable growing demand of clean energy in near future. In the past few decades, tremendous efforts have been devoted to research on organic photovoltaics (OPVs) as the electrochemical and optical properties of OPV materials can be customized through judicious molecular engineering. Though OPV devices gave power conversion efficiencies (PCEs) no more than 0.1% while conceptually demonstrated in late 1950s, nowadays scientists have achieved PCEs over 17% utilizing new material systems and device fabrication techniques. Beside performance, OPVs can be easily fabricated through solution methods and the device properties are highly tunable, facilitating the application of OPVs in next-generation solar energy system. While OPVs demonstrate great potential to efficiently convert light into electricity, yet all solar energy systems possess a major drawback that sun does not provide a constant stream of energy. A proper energy storage system is necessary to be coupled with the solar energy system to store up the energy harvested from sunlight and maintain stable power supply no matter day or night. Li-S battery made of a sulfur cathode and a metallic Li anode is cost-effective for large-scale energy storage due to its high capacity and energy density. However, the infamous “shuttle effect” in sulfur cathode caused by formation of soluble lithium polysulfide (Li2Sx, 3 ≤ x ≤ 8) during charge/discharge strongly inhibits the commercialization of Li-S battery. An effective material system capable of mitigating the shuttle effect is in urgent need. This dissertation elucidates my research efforts on design and synthesis of organic functional materials for OPVs and sulfur cathodes, respectively. The goal of my research aims at establishing novel structure-property relationships and exploiting rationales on molecular designing which may address current challenges in the fields. Chapter 1 gives a brief overview on the evolution of OPV materials and the design principles. Chapter 2 demonstrates the effect of selenium substitution on ladder-type non-fullerene acceptors for polymer solar cells. Chapter 3 explores the possibility of coupling selenium substitution with -alkylation on central donor cores of non-fullerene acceptors as a strategy to further enhance photovoltaic performance. Chapter 4 provides a basic summary on rationales of designing organic materials for the sulfur cathode of Li-S batteries, and shows a class of polymethacrylates designed and synthesized as a component for a self-healing and polysulfide-trapping polyelectrolyte in Li-S batteries.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Li-S Batteries; Organic Functional Materials; Organic Solar Cells; Chemistry; Materials Science; Organic chemistry; Chemistry